Association between dietary intakes of PCBs and the risk of obesity: the SUN project. Issue 9 (23rd April 2014) - Donat-Vargas, C; Gea, A; Sayon-Orea, C; Carlos, S; Martinez-Gonzalez, M A; Bes-Rastrollo, M
Abstract : Background: Polychlorinated biphenyls (PCB) are persistent organic pollutants (POP) that are consumed because of their bioaccumulation through the food chain. Recent studies have suggested the implication of POPs in the development of metabolic diseases such as type 2 diabetes and obesity. However, this relationship is not entirely consistent, and has not been investigated in longitudinal studies. The purpose of this study was to prospectively examine the association between dietary intake of PCBs and the incidence of obesity in the Seguimiento Universidad de Navarra (SUN) Project. Methods: Our study included 12 313 participants without obesity at baseline, who were followed-up for a median of 8.1 years. Dietary intakes of PCBs, expressed as WHO toxic equivalents, were assessed at baseline through a 136-item semiquantitative food-frequency questionnaire. The published concentration levels of PCBs measured in samples of food consumed in Spain were used to estimate intakes. Multivariable Cox regression models were fitted to estimate HRs and 95% CI for incident obesity. Results: During follow-up, we observed 621 incident cases of obesity. After adjustment for total energy intake and additional adjustment for potential confounders, participants in the fifth quintile of PCBs intake were at higher risk of becoming obese (adjusted HR: 1.58; (95% CI 1.21 to 2.06)) compared to those in the first quintile. The linear trend test was statistically significant (p<0.001). Conclusions: Dietary intake of PCBs as estimated using a food frequency questionnaire was associated with a higher incidence of obesity. Nevertheless, further longitudinal studies are needed to confirm our results.